Evaluation methodology and empirical analysis of carbon emission reduction effect of dual-carbon policy - Xiaobao Yu; Wenjing Zhao; Weiyi Wang (Sustainable Energy Research)
Abstract Global warming poses a major threat to human society. In order to realize sustainable development, China has proposed a “dual-carbon” goal and actively taken measures to reduce carbon emissions. However, large-scale thermal power generation still leads to excessive carbon dioxide emissions, and there is an urgent need to assess the effectiveness of carbon emission reduction and make recommendations. Evaluating the effects of carbon reduction policies can help regions understand the current status of carbon reduction measures. Based on the existing carbon emission reduction assessment methods and concentration index models, this paper proposes two models, $$CI(EC)_{t,i}$$ C I ( E C ) t , i and $$CI(CE)_{t,i}$$ C I ( C E ) t , i , which are used to assess the regional carbon emission reduction effect and the level of clean energy power generation, respectively. Based on the results of the models, an empirical analysis was carried out on 30 provinces, cities and autonomous regions in China, to discuss the trend of carbon emission reduction effect and the level of clean energy power generation before and after the policy was proposed. The results of the study show that: all regions of the country show different characteristics in the trend of carbon emission reduction effect and the level of clean energy power generation; most regions of the country show a decreasing trend in industrial carbon emissions and most regions have an increase in clean energy power generation; the clean energy power generation and technological advances can promote the improvement of carbon emission reduction effect, but there is no positive correlation between the level of clean energy power generation and the carbon emission reduction effect; The level of clean energy power generation and the effect of carbon emission reduction have improved significantly in Liaoning and Shaanxi provinces, which have responded more quickly to the dual-carbon policy. The thesis study helps all regions of China to understand the implementation effect and current situation of carbon emission reduction measures, lays a theoretical foundation for the promotion of subsequent carbon emission reduction work, and at the same time looks forward to the future carbon emission reduction work.